Exploring subtitling strategies of metaphor translation from English into Arabic - Sahari, Yousef (Penerbit Universiti Kebangsaan Malaysia, 2024)
The role that metaphors play in conveying meaning and expressing thoughts is undeniable. However, in the context of Arabic, using subtitles in the translation of metaphors has received relatively little attention compared to their presence in literary texts. This study aims to investigate the strategies employed to render metaphors into Arabic. It also tries to explore the extent to which English metaphors in the three films are domesticated or foreignised. By adopting Lakoff and Johnson's (1980) typology of metaphors and Toury’s (2012) translation strategies, this study found that maintaining the same metaphors in Arabic subtitles is the most common strategy that Arabic subtitlers employ, despite the differences between the English language and Arabic language and their cultures. This indicates the essential role of metaphors in conveying meaning, and subtitlers are evidently aware of its importance. The study concludes with some recommendations for further research on metaphor translation.